Principal as Instructional Supervisor: Role of Supervisory Practices in Professional Development of APS&CS and FGEIS Teachers - Sayyam Bin Saeed; Noor ul Ain (UMT Education Review, 2022)
The process of supervision directly impacts teachers and students in a school. The current study revolved around the comparison of instructional supervision practices carried out by the principals of APS&Cs and FGEIs in Pakistan and its impact on professional development of teachers. A quantitative approach was used to conduct the current study. Sampling was carried out through multi-stage stratified random sampling technique. The study comprised 600 teachers and 120 principals from APS&Cs and FGEIs. The data was collected through questionnaires and the reliability was .871 and .766 respectively. Statistical techniques for instance, t-test, standard deviation, and mean were used for the analysis of acquired data. The findings of the study revealed that the concept of supervision is a much broader phenomenon than inspection. Moreover, it is the duty of the heads of institutions to develop interactive, healthy, and accommodating environment for teachers. The principals need to utilize available resources in institutions in such a way that it results in overall enhancement of teaching-learning process. Moreover, the head of institutions should collaborate and guide the teachers. It would help the teachers to reinforce their competencies in field of teaching which would ultimately result in overall performance.